Sentencing guidelines : exploring the English model - Ashworth, Andrew; Roberts, Julian V. (Oxford : Oxford University Press, 2013)
How do sentencing guidelines affect judicial practice? Can public opinion influence the development of these guidelines and what role does the victim have? How do barristers use the guidelines in practice? These questions and more are addressed in this volume examining the English sentencing guidelines and how they function.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Aug 2, 2013).
Keywords: Sentences (Criminal procedure) -- England; Sentences (Criminal procedure) -- Wales